The Function of CD3+CD56+ NKT-Like Cells in HIV-Infected Individuals - Yongjun Jiang (BioMed Research International, 2014)
CD3+CD56+ NKT-like cells are one of the critical effectors in the immune response to viral infection and tumors, but the functional features of NKT-like cells in HIV infection have been rarely reported. In this study, we observed and described the state of NKT-like cell functions in primary HIV-infected individuals (PHIs), chronic HIV-infected individuals (CHIs), long-term nonprogressors (LTNPs), and HIV-negative controls (NCs). The results showed that the percentage of IFN-γ+CD3+CD56+ NKT-like cells was notably higher in LTNPs compared with CHIs, and the proportion of CD3+CD56+ NKT-like cells with dual function (IFN-γ+CD107a+ NKT-like cells) in LTNPs was also much higher than in CHIs. Additionally, the percentages of IFN-γ+CD107a+ NKT-like cells negatively correlated with viral load. Taken together, our data demonstrated that good functions of CD3+CD56+ NKT-like cells in LTNPs likely occurred as a protective mechanism that slows down HIV disease progression.